Association between educational level and health related quality of life in Spanish adults. Issue 2 (1st February 1999) - Regidor, E; Barrio, G; de la Fuente, L; Domingo, A; Rodriguez, C; Alonso, J
Abstract : OBJECTIVE: To analyse differences in health by educational level in Spanish adults by comparing the health dimensions of the SF-36 Heath Survey. DESIGN: Data were taken from the National Survey on Drug Use carried out in February 1996. The information was collected by home personal interview. In addition to measuring the use of legal and illegal drugs and their associated health risks, the health status of the Spanish population was analysed using the Spanish version of the SF-36 Health Survey. MAIN OUTCOME MEASURE: Absolute and standardised differences between mean score on each dimension of the SF-36 Health Survey in each educational group with respect to the group with the highest educational level. RESULTS: Perceived health status declines with decreasing educational level, except in women with second level education who have a higher mean rating than women with third level education on various health dimensions. The absolute differences in perceived health between the different categories of educational level and the reference category become larger with increasing age. The greatest differences by educational level in both men and women were found in mental health and general health among persons 25 to 44 years of age, and in physical function and general health among those 45 to 64 years. In persons aged 65 or older, the greatest differences are seen in physical function and vitality in men, and in bodily pain and emotional role in women. CONCLUSIONS: The influence of educational level on the different dimensions of perceived health may vary by sex.